"Why didn't I know this?": Land education as an antidote to settler colonialism in early childhood teacher education. Issue 3 (3rd July 2021) - Lees, Anna; Tropp Laman, Tasha; Calderón, Dolores
ABSTRACT: Settler Colonialism is marked by the permanent move of mostly European settlers into other territories that requires the ongoing displacement and/or elimination of Indigenous peoples, the enslavement and dispossession of Indigenous peoples from Africa, and the individual ownership of land for capital gain. This displacement and elimination takes place in the curriculum with an impact on what is learned and not learned in schools. To counteract this, we use land education, an educational approach where curriculum starts with Indigenous peoples and Indigenous knowledge, confronting and dismantling anti-Indigenous colonial processes. Land education is a project of imagining just and sustainable futures, but much work must be done to get there. This article shares insights on what aspects of "getting there" looks like in early childhood teacher education.